Proposing Strategies for Efficiency Improvement by Using a Residential Solid Oxide Fuel Cell Co-Generation System in a Small-Scale Apartment Building - Chang, Han; Lee, In-Hee; Zhai, Bin-Qing; Yang, Yi-Jun; Hou, Yao-Long (Frontiers in Energy Research, 2022)
The high levels of energy consumption commonly seen today have severe consequences. For example, energy consumption in buildings traditionally takes the form of electricity generated from fossil fuels, which causes serious air pollution. Hence, the efficient application of clean energy systems in buildings is crucial. An increasing number of small-scale apartment buildings, such as single-room apartments and dormitories, have emerged as modern culture and societal trends have led to a greater number of people living on their own. In this study, two practical methods were proposed to improve the efficiency of solid oxide fuel cell co-generation systems (SOFC–CGSs) in small-scale apartments in Busan, Korea. One method was sharing a single SOFC–CGS among multiple households, and the other was integrating an SOFC–CGS with a photovoltaic (PV) system. The efficiency of the SOFC–CGS is expected to improve under these two operational methods. In addition, the two proposed operational methods were combined to optimize the efficiency of the SOFC–CGS. To verify the proposed methods, various simulations were conducted in this study. Simulation results indicate that each of the proposed methods can improve the efficiency of the SOFC–CGS and save energy to varying degrees.